PENGUJIAN EFISIENSI PASAR MODAL BENTUK LEMAH DI BURSA EFEK JAKARTA PERIODE JANUARI-JULI 2001 - Widjaja, Merlina; Ernawati, Endang (Manajemen dan Bisnis, 2002)
Since 1988, Indonesian capital market, especially Jakarta Stock Exchange has been grown fast. Then, come up questions about capital market efficiency. The capital market is efficient if the securities prices reflecting all available informations and the prices are fair. Thus, investor could not achieve abnormal return. So, with this reasons and facts, the research analyze weak form Indonesia capital market efficiency at Jakarta Stock Exchange in periode January-July 2001. This research used samples 25 emitent. Autocorrelation test, run test, and variance ratio test were used to test the capital market efficiency. The result is that Indonesian capital market is efficient in weak form with 1% significance level. It means that securities movement have random walk pattern. Thus, investors could not achieve abnormal return if just used technical analysis with past securities prices data to predict prices in the future.